INTEGRATION SCIENCE AND ISLAM: A NEW PRODUCT TO FACILITATE TEACHING AND LEARNING IN COLLEGE - Muslim, Buchori; Nahadi, Nahadi; Anwar, Sjaeful (Jurnal As-Salam, 2023)
The dichotomy between science and Islam later became the cause of the decline of Muslim civilization, especially in the field of knowledge. Therefore, some scientists have made an Islamic integrated learning model that will need integrated Islamic teaching materials as a tool and learning resources. This research aims to develop an integrated Islamic enrichment book on transition elements in inorganic chemistry courses. The research was done using the Four Steps Teaching Material Development (4STMD) method, which consists of four steps: the selection step, the structuring step, the characterization step, and the didactic reduction step. At the selection stage, the main source of teaching materials was a book by Sugiyarto, K.H., and Suyanti, Retno, D. (2010), titled Inorganic Metal Chemistry. While at the structuring step, concept maps, macrostructures, and multiple representations of the transition elements were found. In the characterization step, it was found that the concept has a straightforward character with an 85.8% understanding percentage, so the didactic reduction is unnecessary in this study. Teaching material has a percentage of 78% in the feasibility test; the details are 81% on aspects of language, 75% on presentation of the book, 75% on aspects of performance, and 83% on aspects of graphics. It can be concluded that the teaching materials developed are unfit for use. So, in this study, the didactic reduction is not necessary. Teaching material has a percentage of 78% in the characterization test, details 81% on aspects of language, 75% in the presentation aspect of the book, 75% on aspects of performance, and 83% in the graphic aspect. It can be concluded that the teaching materials developed are fit for use. Product development research is needed as a source and medium for integrated Islamic learning.